Stent overlapping and geometric curvature influence the structural integrity and surface characteristics of coronary nitinol stents - Halwani, Dina O.; Anayiotos, Andreas; Kapnisis, Konstantinos (My University, 2013)
Preliminary studies have revealed that some stents undergo corrosion and fatigue-induced fracture in vivo, with significant release of metallic ions into surrounding tissues. A direct link between corrosion and in-stent restenosis has not been clearly established; nonetheless in vitro studies have shown that relatively high concentrations of heavy metal ions can stimulate both inflammatory and fibrotic reactions, which are the main steps in the process of restenosis. To isolate the mechanical effects from the local biochemical effects, accelerated biomechanical testing was performed on single and overlapping Nickel-Titanium (NiTi) stents subjected to various degrees of curvature. Post testing, stents were evaluated using Scanning Electron Microscopy (SEM) to identify the type of surface alterations. Fretting wear was observed in overlapping cases, in both straight and curved configurations. Stent strut fractures occurred in the presence of geometric curvature. Fretting wear and fatigue fractures observed on stents following mechanical simulation were similar to those from previously reported human stent explants. It has been shown that biomechanical factors such as arterial curvature combined with stent overlapping enhance the incidence and degree of wear and fatigue fracture when compared to single stents in a straight tube configuration.
Keywords: Corrosion and anti-corrosives; Fatigue; Coronary arteries--Stenosis--Relapse; Scanning electron microscopy